2021
DOI: 10.1007/s00330-021-08106-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors analysis according to regional distribution of white matter hyperintensities in a stroke cohort

Abstract: Objectives: The spectrum of distribution of white matter hyperintensities (WMH) may reflect different functional, histopathological, and etiological features. We examined the relationships between cerebrovascular risk factors (CVRF) and different patterns of WMH in MRI using a qualitative visual scale in ischemic stroke (IS) patients. Methods:We assembled clinical data and imaging findings from patients of two independent cohorts with recent IS. MRI scans were evaluated using a modified visual scale from Fazek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Associations were significant both for PVH and DWMH with slightly stronger associations for PVH than DWMH like in our analysis [35]. Also, in a cohort of 618 patients with ischemic stroke or transient ischemic attack, hypertension identified in medical records was significantly associated with higher PVH and DWMH in univariable but only with PVH in multivariable analyses adjusted for age and diabetes [7]. Similarly, self-reported hypertension showed a stronger association with PVH than DWMH in 567 patients from a Chinese neurology department examined because of dizziness and headaches [16].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Associations were significant both for PVH and DWMH with slightly stronger associations for PVH than DWMH like in our analysis [35]. Also, in a cohort of 618 patients with ischemic stroke or transient ischemic attack, hypertension identified in medical records was significantly associated with higher PVH and DWMH in univariable but only with PVH in multivariable analyses adjusted for age and diabetes [7]. Similarly, self-reported hypertension showed a stronger association with PVH than DWMH in 567 patients from a Chinese neurology department examined because of dizziness and headaches [16].…”
Section: Discussionsupporting
confidence: 71%
“…Although SVD is regarded as a common cause of cognitive impairment and dementia, its pathophysiology has not fully been elucidated yet [5,6]. Previous studies in general population and patient cohorts demonstrated that next to age, hypertension represents the most important risk factor for WMH [7,8] and cognitive impairment [9] with strict blood pressure (BP) control preventing progression of WMH [10] and cognitive decline [11]. These studies, however, did not look at BP/treatment categories (normotension without antihypertensive treatment, treated to normotension, untreated hypertension, hypertension despite treatment), but analysed hypertension defined as high blood pressure or presence of antihypertensive treatment, included only patients receiving antihypertensive treatment [9][10][11][12], or patients without a need for antihypertensive treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the location of WMH within the brain might correspond to different pathophysiological mechanisms, as reported recently [4,35,36], and thus present different risk factors and epigenetic signatures. To this aim, we may need to combine EWAS with new neuroimaging analytical approaches that improve the ability to capture the true nature of WMH [37,38].…”
Section: Discussionmentioning
confidence: 99%